Communication Pattern "Omahjiwa" Community Counselor in Helping Counselee Who have Anxiety Disorder - Tasya Aurellia Suseno; Martriana Said (LONTAR: Jurnal Ilmu Komunikasi, 2023)
Mental health is an important thing for everyone to have. Because with a healthy mentality, individuals can do their days productively and can also maximize the abilities that exist in themselves. However, since the pandemic came, all activities have stopped and people also need to follow the changes caused by the pandemic. Because of this, people also feel lost and are also worried about what will happen in the future, which eventually leads to excessive worry. At that time the mental health of some people finally felled and along with this, several communities related to mental health issues emerged on social media to help everyone who had mental disorders. One of these communities is OmahJiwa which provides free counseling for everyone who has mental problems, one of which is anxiety disorders. The purpose of this study was to see the pattern of communication and also the effectiveness of interpersonal communication between a counselor and a counselee who has an anxiety disorder. This research uses a post positivist paradigm with a qualitative approach. The concepts used are Communication Patterns and Interpersonal Communication. The results obtained from this study are the OmahJiwa Community Counselors use 4 Communication Patterns (primary, secondary, linear, circular) and use Two-Way Communication Patterns. 5 directions for the effectiveness of Interpersonal Communication that occurs between counselors and counselees, but the most prominent are empathy, support, and positiveness